Thin-walled box beam bending distortion analytical analysis / A Halim Kadarman … [et al.] - Kadarman, A Halim; Shuib, Solehuddin; Hassan, Ahmad Yusoff; Ahmad Zahrol, Muhammad Adib Izzuddin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In this paper, an analytical method for determining the stress-deformation condition of thin-walled box beam subjected to bending condition was developed. Solution by Vlasov method from a stationary condition complementary energy in Stress-form was developed and its adaptation and application through computer software MAPLE was demonstrated. Quick results can be obtained for various geometries, material properties and loading conditions enhancing parametric studies in design. Distortion effect (or shear lag effect) due to flexural bending was also included.